A New Mathematical Model of Heat Equations And its Application on the Agriculture Soil (European Journal of Pure and Applied Mathematics, 2018)
The goal of this paper is to provide a mathematical model which based on numerical simulation applied to heat equations and comparing the obtained results with virtual temperatures results for different depths of the homogeneous agricultural soil. The model was treated through this research that enable to know the degree of soil temperature homogeneous without recourse to tools of measuring physical expensive. The importance of this lies in the agricultural seed germination at temperatures suitable.
Keywords: Numerical model; Finite elements; Temperature fields; Meteorology; Heat-Soil; Agricultural